The Impact of the Antenatal Care (ANC) Group Model on Pregnant Women's Readiness for Childbirth in the Working Area of the Samarang Health Center - Budiarti, Kurniawan Dewi; Sulliyawati, Eti; Sulastini, Sulastini; Badriyah, Suci (Karsa Husada Health Institute Garut, 2024)
Childbirth readiness involves the initial planning process and preparation for childbirth to help the mother be ready.. The Antenatal Care Group is an ANC group that uses the WhatsApp messaging application. ANC sessions at the posyandu can be an alternative opportunity for pregnant women who rarely visit facilities, providing online classes to increase maternal readiness for childbirth sample consisted of 20 respondents per group, with the intervention administered in the intervention group for six days over a two-week period. The results obtained indicate a significant influence of the ANC group models on the readiness of delivery in pregnant women, with a p-value of ?? = 0.05 or .000 ? 0.05. The ANC group models has a significant impact on improving childbirth readiness in the Samarang Garut Health Center work area. The Antenatal Care Group Models can be used as an alternative to increase pregnant women's readiness for childbirth.